Pengelolaan Persediaan Kaca Film Menggunakan Metode Economic Order Quantity (EOQ) - Muhammad Syafri Al Ghozali; Resista Vikaliana (TIN: Terapan Informatika Nusantara, 2023)
CV Jaya Mandiri Motor is a company engaged in the sales and installation services of automotive and building window films, with branches in various cities. CV Jaya Mandiri Motor is an official dealer for various types of window films. Due to the increasing demand for window film installations, it is not uncommon for the CV Jaya Mandiri Motor branch in Kota Metro to experience shortages of window film stock, mainly due to the two-week lead time for ordering window films from the central distributor. Therefore, an optimization of the window film inventory system at the CV Jaya Mandiri Motor branch in Kota Metro is necessary to address the issue of stockouts and maximize the company's profits. In conducting research at the CV Jaya Mandiri Motor branch in Kota Metro, the Economic Order Quantity (EOQ) method is used to determine the most optimal and economical order quantities for each purchasing instance. The research results in the following EOQ values: Heat Protection window film, 98 meters in quantity with a frequency of 3 orders; 3M Black Beauty window film, 171 meters with a frequency of 2 orders; 3M Crystal Line window film, 83 meters with a frequency of 3 orders; Elite/5M window film, 633 meters with a frequency of 1 order; 3D Auto Film window film, 264 meters with a frequency of 2 orders; Black Sun Control window film, 264 meters with a frequency of 1 order; Black Platinum window film, 231 meters with a frequency of 1 order; and Crystal Ice window film, 456 meters with a frequency of 1 order